Pfaffia glomerata: Gallic acid and phenolic compounds determination (Research, Society and Development, 2022)
Pfaffia glomerata, known as ginseng-brasileiro, is a root widely used in folk medicine, being effective against inflammation, rheumatism, and fatigue, in addition to present aphrodisiacs and antidiabetics properties. Among the classes of substances reported for the specie, the phenolic acids, in special gallic acid, has shown positive activity to learning and memory, having a considerable effect against neurotoxic and pro-oxidant substances. Therefore, the article’s objective was to quantify gallic acid in the chloroform and ethyl acetate fractions from P. glomerata. Thus, the aerial parts of ginseng were collected, dried and subjected to extraction with ethanol followed by fractionation with organic solvents in different polarities, obtaining the hexanic, dichloromethane (CHCl3) and ethyl acetate (AcOEt) fractions. Then, gallic acid was identified by TLC and quantified by HPLC in the ethyl acetate fraction. The total phenolic content was determined in the chloroform and ethyl acetate fractions, presenting values of 70,3 mg/g and 118,6 mg/g, respectively. The gallic acid content determined by HPLC in the AcOEt fraction was 904,15 µg/g, while in the CHCl3 fraction it was not possible to quantify. So, the species can be a source of phenolic compounds for possible applications in the pharmaceutical area.